Defending American Religious Neutrality - Andrew Koppelman (Harvard University Press, 2013)
Th e American law of freedom of religion is in trouble, because growing numbers of critics, including a near-majority of the Supreme Court, are ready to cast aside the ideal of religious neutrality. Th is book defends the claim, which unfortunately has become an audacious one, that American religious neutrality is coherent and attractive. Two factions dominate contemporary discussion of these issues in American law. One, whom I’ll call the radical secularists, tend to regard the law of the religion clauses as a fl awed attempt to achieve neutrality across all controversial conceptions of the good—fl awed because it is satisfi ed with something less than the complete eradication of religion from public life. Th e other, whom I’ll call the religious traditionalists, think that any claim of neutrality is a fraud, because law necessarily involves substantive commitments. Th ey believe that there is thus nothing wrong with frank state endorsement of religious propositions: if the state is inevitably going to take sides, why not this one? One side regards religion as toxic and valueless; the other is untroubled by the state’s embrace of an offi cial religion. Neither sees much value in the way American law actually functions. Yet America has been unusually successful in dealing with religious diversity. Th e civil peace that the United States has almost eff ortlessly achieved has been beyond the capacities of many other generally wellfunctioning democracies, such as France and Germany. Even if the American law of religious liberty were entirely incoherent, it might still be an attractive approach to this perennial human problem. Th ere is, however, a logic to the law that its critics have not understood.